Keteladanan Guru dalam Perspektif Al-Qur’an dan Al-Hadist Melalui Implementasi Kurikulum Merdeka - Faisal Faisal; Muslimin; Nurlaila (MGMP PAI SMP BINTAN, 2025)
Modern education demands that teachers play a role not only as instructors but also as role models in shaping students' character. This article aims to describe the importance of teacher role models from the perspective of the Qur'an and Hadith through the implementation of the Independent Curriculum. This study uses a descriptive qualitative approach with a library research method, focusing on analyzing the concept of teacher role models as reflected in the values ​​of the Qur'an and Hadith, and their relevance to the objectives of the Independent Curriculum. The results of the study indicate that teacher role model values ​​derived from Islamic teachings are directly related to strengthening student character as mandated in the Pancasila Student Profile. Teachers in the Independent Curriculum play the role of educators, motivators, inspirators, and mentors who must be able to instill the values ​​of faith, piety, noble character, independence, and creativity in a student-centered learning process. The implementation of teacher role models based on the Qur'an and Hadith is the main foundation in realizing national education goals, especially in shaping a generation with character, religiousness, and adaptability to developments in science and technology in the era of globalization.